70-80-е годы ХIХ века
Изд. вып. при поддержке Междунар. фонда "Культурная инициатива". Экземпляры: ИСК (19970520) / Инвентарный номер: 1020439 / Цена: / Сис.шифр: 85.313(2Р=Рус) / Авт.знак: И 90 / ГРНТИ: 18 / ББК: 85.313(2Р=Рус)5